การพัฒนาแบบวัดกลยุทธ์การเรียนรู้แบบพหุมิติสำหรับนักเรียนมัธยมศึกษาตอนปลาย - ชัยวิชิต เชียรชนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this study was to develop the standardized multidimensional learning strategies scale for upper secondary school students, There were four sub-objectives as follows: 1) to develop the multidimensional learning strategies scale with high construct validity and reliability. The multidimensional analysis and confirmatory factor analysis were applied in order to determine construct validity and reliability of the scale. 2) to compare the efficiency of learning strategies measurement models consisted of (a) Weinstein and Palmer’s Model, (b) Stevens and Tallent-Runnels’s Model, (c) Cano’s Model, and (d) Model developed by the researcher. 3) to assess the prediction of measurement efficiency of students’ learning strategies on academic achievement, and 4) to construct the norms of learning strategies. The sample were 2,187 upper secondary school students from schools under the jurisdiction of the Office of the Basic Education Commission. The instrument for data collection was a multidimensional learning strategies scale for upper secondary school students. The data were analyzed by the SPSS for windows, the Microsoft Office Excel, the ConQuest, and the LISREL program. The findings were as follows: 1. The multidimensional learning strategies scale consisted of three dimensions: cognitive, affective, and skill strategies. The EAP reliabilities of scale were .849, .878, and .844, respectively, and the construct validities of scale were supported by learning strategies model of the multidimensional approach (LSMMA). The LSMMA was a better fitting model than the composite approach (Deviance Statistic of multidimensional approach=56,461.589, composite approach=56,527.426) and the consecutive approach (Akaike Information Criterion of multidimensional approach=56,737.589, consecutive approach=63,750.977). In addition, the model was fit to the empirical data indicated by chi [superscript 2]/=758.582 (df=705, p=.079), GFI=.947, AGFI=.926, RMR=.035, and RMSEA=.011. 2. The model developed by the researcher was the most efficient model consisted of three dimensions as well. This model was identified by chi [superscript 2]/=24.666 (df=17, p=.102), chi [superscript 2]//df=1.451, GFI=.998, AGFI=.993, RMR=.008, RMSEA=.014, CFI=1.000, and AIC=100.666 (Saturated AIC=110.000).3. The skill strategy, affective strategy, and cognitive strategy had significant positive effects on academic achievement. The standardized regression coefficients were .274, .241, and .227, respectively. Each strategy accounted for 7.50, 5.80, and 5.10 percents of variance in the academic achievement. There was low error of prediction for .008, .007, and .010, respectively. 4. The student’s national norm had the cognitive strategy score at the nearly high level (49.06%), nearly low level (41.24%), high level (5.77%), and low level (3.93%), respectively. They had the affective strategy score at the nearly high level (62.46%), nearly low level (20.90%), high level (15.68%), and low level (0.96%), respectively. Also, they had the skill strategy score at the nearly high level (54.73%), nearly low level (26.62%), high level (16.19%), and low level (2.46%), respectively